The Impacts of Climate Change and Price Fluctuations to Income of Rubber Farmers at Burai Village Ogan Ilir - Elly Rosana; Yulius Yulius; Thirtawati Thirtawati; Dewi Paramita (Department of Communication and Community Development Sciences and PAPPI (Perhimpunan Ahli Penyuluh Pertanian Indonesia), 2020)
The objectives of this study to analyzing climate change on rubber productivity in Burai Village and differences in rubber farmers' income and family consumption patterns in Burai Village before and after falling rubber prices. This research was conducted from October to December 2017. This study was a survey research which took 30 samples from 160 rubber farming households using simple random sampling method. The results of this study indicate that climate change has an impact on the productivity of rubber farming in the village of Burai, where there was a decline in rubber productivity by 14.44 percent from 1,345.80 kg / ha in 2012 to 1,151.42 kg/ha in 2016, while farmers' income rubber in 2012 and 2016 decreased by 67.73 percent. The difference in income of rubber farming families in 2012 and 2016 was Rp 6,267,390.6 per year, meaning that there was a decrease of 11.78 percent. Large differences in consumption patterns before and after the decline in rubber prices by Rp 476,933.34 per year or an increase of 1.40 percent compared to 2012, in line with Engel's Theory which states that the smaller a person's income, the greater the income used for food consumption.